Genetic investigation of South Africans with the Noonan Syndrome phenotype using targeted next generation sequencing - Ngongang Tekendo, Cedrik (Division of Human Genetics, 2018)
Introduction: Noonan Syndrome (NS) is an autosomal dominant multisystem disorder, characterised by short stature, distinctive facial dysmorphism, cardiovascular abnormalities and developmental delay. Its estimated incidence is 1:1000 to 1:2500 live births. NS is caused by germline mutations in more than ten genes encoding proteins integral to the Ras/MAPK signaling pathway. Pathogenic variants in these genes account for 70-80% of NS cases. The clinical diagnosis of NS can be challenging in some cases, even when performed by experienced clinicians. The introduction of Next Generation Sequencing (NGS) technology in clinical practice in the Western world has tremendously facilitated the molecular diagnosis of RASopathies. Molecular testing for NS is not yet available in South Africa, nor has any study investigating NS from clinical and molecular perspectives been conducted in South Africans. Aim: The aim of this study was to investigate selected genes within a group of paediatric and adult patients with a clinical diagnosis of NS. Methods: This study was a cross-sectional descriptive study, including twenty-six familial and isolated NS patients recruited in Cape Town in the period January 2015-January 2017. Thorough phenotyping of each patient according to the international diagnostic criteria for NS was followed by targeted NGS, performed on leucocyte DNA samples from sixteen unrelated patients out of the twenty-six included. Sequencing involved all the exons and intron-exon boundaries of a predesigned panel of 14 genes, including A2ML1, BRAF, CBL, HRAS, KRAS, MAP2K1, MAP2K2, NRAS, PTPN11, RAF1, RIT1, SHOC2, SOS1 and SPRED1. Results: Of the 26 patients included, 50% had a family history suggestive of NS. The median age at diagnosis was4.5 years (range: 1month-51years). Individuals of mixed-race ancestry were most represented (53.8%), followed by black Africans (30.8%). The clinical features identified were consistent with those reported in other populations. Compared to other series, our cohort revealed a lower frequency of Pulmonary Valve Stenosis (34.6%) and a less severe developmental phenotype. Variants predicted pathogenic were detected in 7(43.7%) DNA samples out of the 16 analysed. The genes involved were CBL in three cases (42.8%), PTPN11and MAP2K1in two cases (28.6%, for each gene). Surprisingly, the proportion of CBL variants was relatively high compared to those in the literature. Genotype-phenotype correlations showed that clinical features of NS were more typical in patients with pathogenic variants in MAP2K1, and less in those with variants in CBL. Conclusion: This is the first clinical and molecular study in South Africans with the NS phenotype. The phenotype of affected individuals with NS in South Africa is globally similar to that reported in the literature. Therefore, the use of international diagnostic criteria can effectively enable the clinical diagnosis of NS in most South African patients. These preliminary data suggest that the distribution of pathogenic variants in NS genes in South Africans may be different from that reported in other populations. Finally, this study demonstrates that Targeted NGS can be successfully applied to the molecular diagnosis of NS and related conditions in South Africa, and should be implemented in clinical practice.